Study vs. Work: Examining Conflict and Burnout Among Students at UIN Sayyid Ali Rahmatullah Tulungagung - Arifah, Zannuba (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2023)
Working students often face challenges in balancing their roles as learners and employees, known as work-study conflict. This imbalance can lead to burnout, a condition characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment. This study aims to analyze the effect of work-study conflict on burnout among working students at UIN Sayyid Ali Rahmatullah Tulungagung. A quantitative approach with a causal-comparative design was employed. The sample consisted of 100 working students selected through purposive sampling, with criteria including working at least 15 hours per week and aged 20-25 years. Data were collected using questionnaires comprising a work-study conflict scale based on Markel & Frone's (1998) theory and a burnout scale derived from Maslach & Leiter's (2016) model. Simple linear regression analysis revealed that work-study conflict significantly affects burnout, contributing 14.2% (R² = 0.142). Each unit increase in work-study conflict raised burnout by 0.779 units. These findings indicate that working students experiencing higher levels of conflict are at greater risk of burnout. However, most of the variation in burnout (85.8%) is influenced by other unexamined factors. This study concludes that managing role conflicts is crucial to mitigating burnout risks. Universities are encouraged to provide support programs such as time management training, counseling services, and flexible class schedules. Future research should explore additional variables, such as social support or coping strategies, using a mixed-method approach for a more comprehensive understanding.